AN EVOLUTIONARY VIEW OF DEFENCE (Journal of the Spanish Institute for Strategic Studies, 2018)
This article analyses the defence case from the perspective of evolutionaryeconomics. To this end, the key elements of this theory have been appliedto the issue of defence; in other words, to the development of militarycapabilities for the purpose of efficiently protecting society from externalthreats within a framework of uncertainty and bounded rationality ofthe actors involved. The paper describes the evolving way through whichsuch capabilities are developed, including the means required for theirfunctioning. Finally, we present the conclusions drawn from this analysistogether with its resulting practical implications.